The Spanish prisoner - Tzioumakis, Yannis (American indies., 2009)
Despite more than a passing nod to such crowdpleasing classics as Hitchcock's North by Northwest, playwright-turned-independent filmmaker David Mamet's The Spanish Prisoner is a particularly idiosyncratic film that betrays its origin outside the Hollywood mainstream. Featuring a convoluted narrative, an excessive, often anti-classical, visual style, and belonging to the generic category of the'con game film' which often challenges the spectator's cognitive skills, The Spanish Prisoner is a film that bridges genre filmmaking withpersonal visual style, independent film production with niche distribution, and mainstream subject matter with unconventional filmic techniques. This book discusses The Spanish Prisoner as an example of contemporary American independent cinema while also using the film as a vehicle to explore several key ideas in film studies, especially in terms of aesthetics, narrative, style, spectatorship, genre and industry. Key Features Distinguishes between independent and 'indie' cinema through anexamination of the 'classics divisions, ' especially Sony Pictures Classics Assesses the position of David Mamet within American cinema Introduces the genre categories of the 'con artist' and the 'con game' film and discusses The Spanish Prisoner as a key example of the latter Examines the ways in which narrative, narration and visual style deviate from the mainstream/classical aesthetic Yannis Tzioumakis Lecturer in Media and Communication Studies at theUniversity of Liverpool.